2014
DOI: 10.1017/s136672891400087x
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism delays clinical manifestation of Alzheimer's disease

Abstract: The current study investigated the effects of bilingualism on the clinical manifestation of Alzheimer's disease (AD) in a European sample of patients. We assessed all incoming AD patients in two university hospitals within a specified timeframe. Sixty-nine monolinguals and 65 bilinguals diagnosed with probable AD were compared for time of clinical AD manifestation and diagnosis. The influence of other potentially interacting variables was also examined. Results indicated a significant delay for bilinguals of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 30 publications
9
116
2
4
Order By: Relevance
“…Similar results were reported in cognitive aging (n=232) (Perquin et al, 2013) and dementia (n=134) (Woumans et al, 2014). Thirdly, in large parts of the world bilingualism is the rule rather than exception.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Similar results were reported in cognitive aging (n=232) (Perquin et al, 2013) and dementia (n=134) (Woumans et al, 2014). Thirdly, in large parts of the world bilingualism is the rule rather than exception.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Crucially, older bilingual individuals manifest symptoms of AD significantly later than comparable monolinguals (13)(14)(15), with an approximate delay of 4.5 y. Furthermore, bilingual speakers also show significantly better cognitive recovery following stroke than monolinguals (16).…”
mentioning
confidence: 97%
“…Conversely, retrospective studies which have investigated age of onset or diagnosis in individuals already diagnosed with the disease have typically reported that bilingualism delays the development of dementia (Alladi et al, 2013;Bialystok et al, 2007;Craik et al, 2010;Gollan et al, 2011;Woumans et al, 2015). Generally, prospective studies are preferred to retrospective studies as they are less affected by potential confounds such as recall bias, where individuals recall details incorrectly (Guzmán-Vélez & Tranel, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, as Bialystok et al suggested (2007), there is no reason why bilinguals would be more likely to recall information differently to monolinguals. Furthermore, age of diagnosis was determined by medical records in these studies (Alladi et al, 2013;Bialystok et al, 2007;Craik et al, 2010;Gollan et al, 2011;Woumans et al, 2015), which are unlikely to contain false information. Nevertheless, further research is needed to explore why strikingly different findings have been reported using prospective and retrospective studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation